A critical review on design aspects and developmental status of metal hydride based thermal machines. (13th September 2018) - Muthukumar, P.; Kumar, Alok; Raju, Nithin N.; Malleswararao, K.; Rahman, Muhammad M.
Abstract: Over two decades, research in the field of metal hydride based thermal machines has gained immense attention by the researchers of different fields. Because of its capability to store large volume of hydrogen per unit mass at near ambient condition, its utilization has been spread in numerous applications such as energy storage and other biological, chemical, aerospace and nuclear applications. Though there have been several review reports published on metal hydride based hydrogen storage, but the present work is focused on the thermal management issues and worldwide developmental status of various metal hydride based thermal machines such as thermal energy storage, heat upgradation, heat pump, cooling system, and hydrogen purification and compression. With a brief discussion about the basic understanding of metal hydride alloy formation, this paper also covers screening of metal hydride alloys, design considerations and evolution of different reactor geometries for various metal hydride based thermal management systems. The review also addresses the benefit of coupling of a metal hydride based hydrogen energy system with a conventional thermal system in order to a produce hybrid system with much higher performance and almost zero environmental pollution. Graphical abstract: Image 1 Highlights: Summarised the world wide developmental status of various MH based thermal machines. Critically reviewed the thermal modeling of various MH based thermal machines. Various heat transfer enhancement techniques used in MH beds are discussed. Selection procedure of MH alloys for various engineering applications are presented. Issues related to the commercialization of MH based applications are discussed.